Challenges in the Methodology of the Process of Strategic Analysis in the Context of Cooperation and the Development of New Organizational Forms of Enterprisesa - Błaszczyk, Marek (Studia Oeconomica Posnaniensia, 2019)
The author asks questions about the validity and adequacy of classic methods and procedures of the process of strategic analysis and the conditions for using classical tools in new areas. Due to the growing number of tools of strategic analysis, the author focuses on the procedural aspects of the strategic analysis process. The article is conceptual in character and is based on secondary research. These studies focus on three aspects: 1) identification of the most important conditions of cooperation processes, 2) analysis of previously carried out research in the Resource-Based View (RBV) perspective; and 3) assessment of the current state of knowledge in the field of standards for the process of strategic analysis.